Reversible Dehalogenation in On‐Surface Aryl–Aryl Coupling. Issue 33 (28th May 2020) - Stolz, Samuel; Di Giovannantonio, Marco; Urgel, José I.; Sun, Qiang; Kinikar, Amogh; Borin Barin, Gabriela; Bommert, Max; Fasel, Roman; Widmer, Roland
Abstract: In the emerging field of on‐surface synthesis, dehalogenative aryl–aryl coupling is unarguably the most prominent tool for the fabrication of covalently bonded carbon‐based nanomaterials. Despite its importance, the reaction kinetics are still poorly understood. Here we present a comprehensive temperature‐programmed x ‐ray photoelectron spectroscopy investigation of reaction kinetics and energetics in the prototypical on‐surface dehalogenative polymerization of 4, 4′′‐dibromo‐ p ‐terphenyl into poly( para ‐phenylene) on two coinage metal surfaces, Cu(111) and Au(111). We find clear evidence for reversible dehalogenation on Au(111), which is inhibited on Cu(111) owing to the formation of organometallic intermediates. The incorporation of reversible dehalogenation in the reaction rate equations leads to excellent agreement with experimental data and allows extracting the relevant energy barriers. Our findings deepen the mechanistic understanding and call for its reassessment for surface‐confined aryl–aryl coupling on the most frequently used metal substrates. Abstract : To reverse or not to reverse : The initiating dehalogenation step in on‐surface dehalogenative aryl–aryl coupling is evidenced to be reversible on Au(111), but not on Cu(111). This calls for a reassessment of reaction pathway and kinetics and discloses conditions to overcome current limitations in on‐surface synthesis.